2023
DOI: 10.1111/dom.15039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of predictive factors of diabetic ketoacidosis in type 1 diabetes using a subgroup discovery algorithm

Abstract: Aim: To identify predictive factors for diabetic ketoacidosis (DKA) by retrospective analysis of registry data and the use of a subgroup discovery algorithm.Materials and Methods: Data from adults and children with type 1 diabetes and more than two diabetes-related visits were analysed from the Diabetes Prospective Follow-up Registry. Q-Finder, a supervised non-parametric proprietary subgroup discovery algorithm, was used to identify subgroups with clinical characteristics associated with increased DKA risk. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ [5] , [6] , [7] , [8] , [9] , [10] , [11] ], have been applied to the medical domain. Recent studies use subgroup discovery to identify subgroups of cancer patients [ 14 , 15 ], identify predictive factors for diabetic ketoacidosis [ 16 ], or discover subgroups of patients undergoing transcatheter aortic valve implantation with high model prediction error and their distribution over the centres [ 17 ]. Gamberger et al [ 11 ] demonstrated the applicability of SGD analysis for in brain ischaemia.…”
Section: Related Workmentioning
confidence: 99%
“…[ [5] , [6] , [7] , [8] , [9] , [10] , [11] ], have been applied to the medical domain. Recent studies use subgroup discovery to identify subgroups of cancer patients [ 14 , 15 ], identify predictive factors for diabetic ketoacidosis [ 16 ], or discover subgroups of patients undergoing transcatheter aortic valve implantation with high model prediction error and their distribution over the centres [ 17 ]. Gamberger et al [ 11 ] demonstrated the applicability of SGD analysis for in brain ischaemia.…”
Section: Related Workmentioning
confidence: 99%
“…It was defined as hyperglycemia (blood glucose level greater than 13.9 mmol/L or greater than 250mg/dl and any of the following: venous PH less than 7.3 or bicarbonate less than 15 mmol/L). In addition, clinical signs and symptoms of volume depletion, Kussmaul breathing, cerebral edema, acetone or fruity breath odor, mental status alterations, vomiting, nausea, and infection are indicators of DKA (2,3).…”
Section: Introductionmentioning
confidence: 99%